What is addiction? - Ross, Don, 1962- (Cambridge, Mass. : MIT Press, 2010)
"The image of the addict in popular culture combines victimhood and moral failure; we sympathize with addicts in films and novels because of their suffering and their hard-won knowledge. And yet actual scientific knowledge about addiction tends to undermine this cultural construct. In What Is Addiction? leading addiction researchers from neuroscience, psychology, genetics, philosophy, economics, and other fields survey the latest findings in addiction science. They discuss such questions as whether addiction is one kind of condition, or several; if addiction is neurophysiological, psychological, or social, or incorporates aspects of all of these; to what extent addicts are responsible for their problems, and how this affects health and regulatory policies; and whether addiction is determined by inheritance or environment or both."--BOOK JACKET.
Neuroeconomics of addiction : the contribution of executive dysfunction / Warren K. Bickel and Richard Yi -- Neurobiology of pathological gambling / Jennifer D. Bellegarde and Marc N. Potenza -- Genetic influences on addiction : alcoholism as an exemplar / James MacKillop, John E. McGeary, and Lara A. Ray -- Addiction as a breakdown in the machinery of decision making / A. David Redish -- Economic models of pathological gambling / Don Ross -- Addiction : a latent property of the dynamics of choice / Gene M. Heyman -- Addiction and altruism / Howard Rachlin -- The core process in addictions and other impulses : hyperbolic discounting versus conditioning and cognitive framing / George Ainslie -- Measuring dispositions to bundle choices / David Spurrett and Ben Murrell -- Neural recruitment during self-control of smoking : a pilot fMRI study / John R. Monterosso ... [et al.] -- Anticipatory processing as a transdisciplinary bridge in addiction / Mark S. Goldman ... [et al.] -- Impulsivity and its association with treatment development for pathological gambling and substance use disorders / Nancy M. Petry -- Medical models of addiction / Harold Kincaid and Jacqueline A. Sullivan -- Addiction and the diagnostic criteria for pathological gambling / Neil Manson -- Irrational action and addiction / Timothy Schroeder -- Defining addiction and identifying the public interest in liberal democracies / Peter Collins.
"A Bradford book."
Includes bibliographical references and index.
Keywords: Substance abuse; Compulsive behavior; Cognitive neuroscience; Neurosciences -- Social aspects; Substance-Related Disorders -- physiopathology; Behavior, Addictive -- physiopathology; Behavior, Addictive -- psychology; Gambling -- psychology; Neurobiology; Substance-Related Disorders -- psychology